Economic Effects of Sports Events in Tourism. Case Study EURO 2024 - CONSTANTINESCU, Mădălina; UNGUREANU, Lorin (Journal of Environmental Management and Tourism; Vol 15 No 4 (2024): JEMT, Volume XV, Issue 4(76), Winter 2024DO - 10.14505/jemt.v15.4(76).08, 2024)
Major sporting events such as the Olympic Games, European Championships, the Asian Cup, World Championships, and other international competitions have become not only moments of joy but also powerful economic drivers. These events extend beyond competitions on the field, having a significant impact on the economy and tourism of the host country. The professional organization of sporting competitions is highly beneficial for the public image of the host country and cities, as well as for local businesses involved in the event organization process. The results include revenue, eventual profit, increased occupancy rates, greater use of accommodation services, taxes and fees collected for the state budget, job creation, and an excellent boost in public image. UEFA EURO 2024 was one of the most spectacular sporting events of the year, bringing football fans together from around the world. With Germany as the host country, this competition not only offered world-class football matches but also provided a unique opportunity to explore the culture and attractions of this European nation. Whether in Berlin, Munich, Frankfurt, Hamburg, or Cologne, each host city provided unique experiences that enriched the journey for fans from all over. From culinary delights to must-see tourist attractions, unforgettable moments were created throughout Germany. This article aims to highlight the importance of major sporting events and their impact on the local economy. It also discusses the direct impact of sports tourism on various economic sectors and how it stimulates the overall economy.